The figure of the affective referent: the time factor and the notion of socioaffectivity - Galletti, Judith (Universidad Nacional del Litoral, 2020)
The rule of Article 607 of the Civil and Commercial Code that’s regulates the figure of the affective referent only allows to grant a legal framework to the personal relationship between the child and his affective referent through two institutions, the guard and the guardianship, leaving out the adoption. Similarly, the strict prohibition of de facto guard that introduces article 611 of the Civil and Commercial Code inhibit the possibility of adoption, preventing the consideration of situations in which an affective bond was created between the child and his/her carer, which would contradict the principle of the best interests of the child that must be imposed in all decisions.